Effects of Dietary Nitrates on Systemic and Cerebrovascular Hemodynamics. (25th December 2013) - Bond, Vernon; Curry, Bryan H.; Adams, Richard G.; Asadi, M. Sadegh; Millis, Richard M.; Haddad, Georges E.
Abstract : Cerebral blood flow dysregulation is often associated with hypertension. We hypothesized that a beetroot juice (BRJ) treatment could decrease blood pressure and cerebrovascular resistance (CVR). We subjected 12 healthy females to control and BRJ treatments. Cerebrovascular resistance index (CVRI), systolic blood pressure (SBP), total vascular resistance (TVR), and the heart rate-systolic pressure product (RPP) measured at rest and at two exercise workloads were lower after the BRJ treatment. CVRI, SBP, and RPP were lower without a lower TVR at the highest exercise level. These findings suggest improved systemic and cerebral hemodynamics that could translate into a dietary treatment for hypertension.